Efektifitas Ta'zīr Imārah Syu'ūn Al-Ṭalabah (IST) Dalam Mendisiplinkan Santri Pondok Pesantren IslamAl-Mukmin Dukuh Ngruki Desa Cemani Kec. Grogol Kab. Sukoharjo Tahun 2016 - Bashari, Muh. Azam Khasanal; , Dra. Chusniatun, M.Ag (2016)
Historically Islamic boarding school is the oldest Islamic educational institution in Indonesia. So far, pondok pesantren is recognized to be able to give coaching and education for students. The results of boarding school's coaching proves that the students have social, religious and educational values. One of the recent boarding school is Islamic Boarding School Al-Mukmin which is located in Sukoharjo. Islamic Boarding School of Al-Mukmin has an organization named Imārah Syu'ūn Al-Ṭalabah (IST) which regulates the students' activities in worship, cleanliness, security, and language. The organizers of IST find some members obeying the rule while others breaking the rule. In facing the students who break the rule, IST applies the implementation of ta'zīr (punishment). The problem statements of this research are how the implementation of ta'zīr of Imārah Syu'ūn Al-Ṭalabah (IST) in disciplining the students of Islamic Boarding School Al-Mukmin in 2016 is and how the effectiveness of ta'zīr in disciplining the students of Islamic Boarding School of Al-Mukmin in 2016 is. Then, the purposes of this research are to describe the implementation of ta'zīr of Imārah Syu'ūn Al-Ṭalabah (IST) in disciplining the students of Islamic Boarding School of Al-Mukmin in 2016 and to describe its effectiveness in disciplining the students of Islamic Boarding School of Al-Mukmin in 2016. This research is a field research in Islamic Boarding School of Al-Mukmin. This research uses a qualitative approach by implementing the method of descriptive analysis. The methods of data collection which are used are interview, documentation and observation. Meanwhile, to analyze the results of this research, the approach of descriptive qualitative analysis is used, consisting of four activities, they were: elucidating all data from many sources (interview, observation, and documentation), reducing the data and then filtering them in accordance with the theory and problem statements, presenting the data in the form of narration, and drawing the conclusion. The results of this research show that one of the purposes of the rule existence in pesantren is to create discipline students. The ways to discipline them are through discipline of time, discipline of learning, and discipline of behavior. Nevertheless, there are some students who break the rule and finally, they must be given ta'zīr/punishemt. Ta'zīr given by IST are adjusted to the kinds of infraction, they are: light infraction, moderate infraction, heavy infraction, and very heavy infraction. The students tend to do the light infractions such as being late to go to the mosque and not using the official languages (Arabic-English). The implementation of punishement/ta'zīr of IST is directed to how to form discipline in the students. Actually, the implementation of this ta'zīr is very effective and is still in a reasonable limit. Its orientation is directed to guidance and improvement toward betterment. Keywords: Effectiveness, Ta'zīr, Disciplining